Dancing with the Giants: China, India, and the Global Economy - Winters, L. Alan (Washington, DC : World Bank, 2012)
This report takes a dispassionate and critical look at the rise of China and India, and asks questions about this growth: Where is it occurring? Who is benefiting most? Is it sustainable? And what are the implications for the rest of the world? The book considers whether the giants' growth will be seriously constrained by weaknesses in governance, growing inequality, and environmental stresses, and it concludes that this need not occur. However, it does suggest that the Chinese and Indian authorities face important challenges in keeping their investment climates favorable, their inequalities at levels that do not undermine growth, and their air and water quality at acceptable levels. The authors also consider China's and India's interactions with the global trading and financial systems and their impact on the global commons, particularly with regard to climate. The book finds that the giants' growth and trade offer most countries opportunities to gain economically. However, many countries will face strong adjustment pressure in manufacturing, particularly those with competing exports and especially if the giants' technical progress is strongly export- enhancing. For a few countries, mainly in Asia, these pressures could outweigh the economic benefits of larger markets in, and cheaper imports from, the giants; and the growth of those countries over the next fifteen years will be slightly lower as a result. The giants will contribute to the increase in world commodity and energy prices but they are not the principal cause of higher oil prices. The giants' emissions of CO2 will grow strongly, especially if economic growth is not accompanied by steps to enhance energy efficiency. At present, a one-time window of opportunity exists for achieving substantial efficiency improvements if ambitious current and future investment plans embody appropriate standards. Moreover, doing so will not be too costly or curtail growth significantly. From their relatively small positions at present, the giants will emerge as significant players in the world financial system as they grow and liberalize. Rates of reserve asset accumulation likely will slow, and emerging pressures will encourage China to reduce its current account surplus.